EFFICACY OF COGNITIVE REHABILITATION THERAPY ON POST-STROKE DEPRESSION AMONG SURVIVORS OF FIRST STROKE ATTACK IN IBADAN, NIGERIA (2014)
Post-Stroke Depression (PSD) is one of the commonest complications of stroke. There is no clear evidence that PSD is either related to stroke etiologically or an independent disorder. However, there is no adequate treatment for PSD to alleviate the sufferings of survivors. This study was designed to examine the efficacy of Cognitive Rehabilitation Therapy (CRT) in the treatment of PSD among survivors of first stroke attack at the University College Hospital (UCH), Ibadan, Nigeria. The Bio-psychosocial theory provided the theoretical basis. The study involved a survey, using cross-sectional ex-post facto design and experimental design. For the survey, 90 clinically diagnosed patients were purposively selected at the Medical Out-Patient (MOP), and Physiotherapy clinics of UCH. A questionnaire which focused on Beck Depression Inventory (BDI), Health Orientation (HO), Barthel Index (BI), Perceived Social Support Scale (PSSS), Health Locus of Control Scale (HLCS), Stroke Impact Scale (SIS), Hospital Anxiety & Depression Scale (HADS) and Stressful Event Scale (SES) was administered, while the result of Computer Tomography and prior illness were retrieved from the hospital records. For the experiment, 30 participants with high scores on poststroke depression were randomly assigned into 3 groups of 10 participants each namely: Cognitive Rehabilitation Therapy (CRT) and Psycho-Education (PE) and Control Group (CG). Cognitive Rehabilitation Therapy consisted of nine sessions with first three sessions focusing on activity stimulation, second three focusing on negative thoughts and the third focusing on people contacts and Psycho-Education (PE) of nine sessions focusing on knowledge on stroke and post-stroke depression and Control (CG) group on waiting list. The BDI scale was used for assessing PSD at post-test. Analysis of co-variance, multiple regression, two way ANOVA, t-test of independent samples were the statistical data analyses techniques adopted at p? 0.05. The study had 38 males and 52 females with mean age of 57.33 years (SD±12.72). Social support significantly influenced level of PSD. There was significant interaction effect of age and level of physical dependency on PSD with younger survivors with physical dependence having higher post-test PSD (11.8 ±7.79) than older survivors with physical dependence (11.4 ±8.48). Locus of control and location of hemispheric lesion did not predict PSD. Brain lesion, physical disability and health orientation did not jointly or independently predict PSD (r = 0.27, ?=-0.69, 0.25, -0.09). Also, patients age, prior illness and concordance did not predict PSD jointly or independently (r=0.26, ?=-0.09,-0.02,-0.18). There was significant difference in the efficacy of CRT, PE and CG on PSD, with CRTCG mean difference of (-9.4±3.11), PECG (1.0±3.83). Furthermore, stress was not a confounding variable on the efficacy of CRT. Type of therapy significantly influenced PSD at post-test, with the CRT having greater mean reduction to CG (-11.1±3.1) than PE to the CG (3.0 ±3.8). Cognitive rehabilitation therapy with culture tailored modules significantly reduced post-stroke depression. Hence, cognitive rehabilitation therapy should be integrated as adjunct treatment of post-stroke depression in clinical practice for enhanced clinical management of stroke survivors.